2015
DOI: 10.18632/oncotarget.6402
|View full text |Cite
|
Sign up to set email alerts
|

Implications of a peroxisome proliferator-activated receptor alpha (PPARα) ligand clofibrate in breast cancer

Abstract: Inflammatory and invasive breast cancers are aggressive and require better understanding for the development of new treatments and more accurate prognosis. Here, we detected high expression of PPARα in human primary inflammatory (SUM149PT) and highly invasive (SUM1315MO2) breast cancer cells, and tissue sections of human breast cancer. PPARα ligands are clinically used to treat dyslipidemia. Among lipid lowering drugs clofibrate, fenofibrate and WY14643, clofibrate showed high chemo-sensitivity towards breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 47 publications
1
52
0
Order By: Relevance
“…It also serves as a potential diagnostic and prognostic biomarker as it is secreted in the blood of patients with breast, prostate, colon and ovarian cancers compared with normal healthy subjects [69]. In our recent study we demonstrated that compared to HMEC, SUM149PT and SUM1315MO2 breast cancer cells express increased level of FASN [70]. We have several interesting findings in the context of paracrine signaling in the OPG rich breast cancer microenvironment that drives carcinogenesis via inducing and sustaining inflammatory cycloxygenase-2 (COX-2) and lipogenic FASN in an invasive breast cancer setting (Figure 3) (unpublished results).…”
Section: Opg and Its Binding Partners In Breast Cancer Cellsmentioning
confidence: 99%
“…It also serves as a potential diagnostic and prognostic biomarker as it is secreted in the blood of patients with breast, prostate, colon and ovarian cancers compared with normal healthy subjects [69]. In our recent study we demonstrated that compared to HMEC, SUM149PT and SUM1315MO2 breast cancer cells express increased level of FASN [70]. We have several interesting findings in the context of paracrine signaling in the OPG rich breast cancer microenvironment that drives carcinogenesis via inducing and sustaining inflammatory cycloxygenase-2 (COX-2) and lipogenic FASN in an invasive breast cancer setting (Figure 3) (unpublished results).…”
Section: Opg and Its Binding Partners In Breast Cancer Cellsmentioning
confidence: 99%
“…Unlike what stated so far, PPARα activation could be useful to fight tumor progression in some tissue, as evidenced in melanoma [78]; in addition to positively affect transcription of FAO enzymes, PPARα is able to decrease transcription of fatty acid synthesis genes. Chandran et al reported favourable results on the protective roles of the PPARα agonist, clofibrate, in discouraging breast cancer inflammation and invasion [121]. They used two triple negative breast cancer cell line, SUM149PT and SUM1315MO2, the first from invasive ductal carcinoma of a patient with inflammatory breast cancer, and the second from highly invasive breast cancer specimen of patient with skin metastasis.…”
Section: Pparα and Cancer Metabolismmentioning
confidence: 99%
“…SREBP-1c (sterol regulatory element binding protein 1c) plays an important role in regulation of de novo fatty acid synthesis, while its cognate SREBP-2 regulates genes of the cholesterol metabolism [123], SREBPs pathway has a key role in fatty acid de novo synthesis of prostate cancer cells [124]. In addition to impairment of lipid synthetic pathway, such as SREBPs, the activation of PPARα by clofibrate was able to up-regulate CPT-1a (first enzyme in FAO) and to reduced the onco-protein levels, such as NF-kB and Erk1/2, in breast cancer cells derived from high metastatic inflammatory tumor specimens [121]. Some evidences indicated PPARα activation as a possible trigger of ineffective tumor metabolism, it was reported that fenofibrate (PPARα agonist) treatment, on cell line and mouse model of oral cancer, supported hexokinase II and VDAC (voltage-dependent anion channel) dissociation, this event destabilized Warburg effect and provided a metabolic switch to OXPHOS, furthermore affected protein expression levels of hexokinase II, PDH and VDAC [125][126][127].…”
Section: Pparα and Cancer Metabolismmentioning
confidence: 99%
“…In some studies, PPAR α inhibits breast cancer progression, promoting apoptosis of cancer cells through NF κ B signalling. Recently, it was demonstrated that clofibrate presents a high chemosensitivity towards breast cancer cells, in all likelihood through the inhibition of NF- κ B and ERK1/2 activation, which lowers cyclin D1, cyclin A, and cyclin E and induces proapoptotic P21 levels [59]. In contrast, in other studies PPAR α promoted breast cancer progression by releasing leukotriene B4 that activates PPAR α in B cells, inducing the differentiation of B cells and metastasis [60].…”
Section: Pparα and Tumorigenesismentioning
confidence: 99%